Anti-DENV-2 Activity of Ethanolic Extracts from Arachis hypogaea L.: Peanut Skin as a Relevant Resource of Bioactive Compounds against Dengue Virus - Menis Candela, Florencia (2024)
Dengue is an emerging disease of high impact on human health. Plants are an important source of new antivirals and Arachis hypogaea stands for its biological properties. The aim of this study was to evaluate the cytotoxicity and antiviral activity and elucidate the antiviral mechanism of ethanolic extracts from A. hypogaea against dengue virus 2 (DENV-2). The skin or tegument ethanolic extract (TEEs) and seed ethanolic extract (SEEs) were obtained. Cytotoxicity was evaluated by MTT and Neutral Red Uptake (NRU). Antiviral activity was evaluated at different stages of the viral replication cycle by the lysis plaque reduction method. The 50% inhibitory concentration (IC50) and selectivity index (SI) were determined. Antiviral activity was further determined by RT-qPCR. The CC50 values were 169 (NRU) and 65 (MTT) µg/mL for TEE. In addition, the CC50 values were >1400 (NRU) and 636 (MTT) µg/mL for SEE. The TEE demonstrated 99.9 ± 0.1% viral inhibition. The TEE presented an IC50 = 3.47 and SI of 48.7 (NRU) and 18.73 (MTT). Its mechanism of antiviral action is broad and it acts in the viral adsorption?penetration stage and inhibits the first steps of infection in the post-penetration stage. It is also capable of acting as virucidal and as prophylactic. Studies of RT-qPCR indicated that the TEE inhibited viral RNA synthesis. These findings suggest that the TEE from A. hypogaea could be a promising antiviral candidate for treating DENV-2 infections.